Clinical outcomes and complications of surgical interventions for multiple myeloma lesions in the extremities and pelvis: A retrospective clinical study - EROL, BÜLENT; TOPKAR, OSMAN MERT (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2021)
Objective: This study aimed to assess the pain and functional status of patients who underwent various surgical interventions for the stabilization of selected multiple myeloma (MM) lesions in the extremities and pelvis and to investigate the rate of complications requiring reintervention. Methods: Patients with MM who underwent various surgical interventions for the extremity or pelvic lesions were retrospectively reviewed. Change in the pain intensity was assessed using visual analogous scale (VAS) preoperatively, at the time of discharge, and at the final follow-up. Functional status was assessed using the musculoskeletal tumor society (MSTS) scoring system for both upper and lower extremities preoperatively and at the final follow-up. Postoperative complications requiring reintervention, including dislocation, loss of fixation/aseptic loosening of prosthesis, mechanical insufficiency, periprosthetic fracture, infection, or progression of the local disease, were recorded. Results: A total of 49 (20 men and 29 women) previously (23) or newly (26) diagnosed patients with a mean age of 60.8 +/- 18.2 years were included in this study. Of these, 6 patients underwent multiple surgeries for different skeletal sites; in total, 57 procedures were performed. The mean follow-up was 47.7 +/- 21.63 months. The lesions were localized to the humerus (19), radius (1), pelvis (4), femur (30), and tibia (3). The surgical indications included therapy-refractory pain for 17 patients and pathological fractures due to progression of pre-existing lesions for 12 patients or newly diagnosed lesions with extensive bone destruction at initial presentation for 28 patients. Surgical procedures included prosthetic reconstruction in 32 patients, cement-augmented osteosynthesis in 9, and closed intramedullary nailing in 16. The mean VAS score decreased from 8.75 +/- 1.2 preoperatively to 3.21 +/- 1.56 at the time of discharge and 1.2 +/- 0.42 at the final follow-up. Although a significant decrease was detected between the preoperative and postoperative VAS scores at the time of discharge (p=0.0001), the decrease between the time of discharge and the final follow-up was statistically insignificant (p=0.086). The mean MSTS score significantly improved from 9.1%+/- 6.4% (range: 0%-40%) preoperatively to 76%+/- 14.9% (range: 40%-93.3%) at the final follow-up (p=0.0001). Significantly higher MSTS scores were obtained in the upper extremity than lower extremity/pelvis (p=0.04) and in isolated diaphyseal involvement than metaphyseal or articular involvement (p=0.032). A total of 11 complications requiring reintervention (19.2%) were observed, which included dislocation (3.5%), loss of fixation (5.2%), mechanical insufficiency (3.5%), infection (5.2%), and local tumor progression (1.7%). The rate of complications requiring reintervention was lower but statistically insignificant in the upper extremity (5%; 1/20) than lower extremity/pelvis (27%; 10/37) (p=0.076) and in isolated diaphyseal involvement (6.2%; 1/16) than metaphyseal or articular involvement (24.3%; 10/41) (p=0.079). Conclusion: Although different types of surgeries can achieve pain relief and good function in different anatomical localizations, better functional results with lower complication rates may be obtained following surgical management of MM lesions in the upper extremities and in diaphyseal localizations.
Keywords: Multiple myeloma; Surgical treatment; Functional outcomes; Complications; PATHOLOGICAL FRACTURES; BONE-DISEASE; METASTATIC-DISEASE; SURVIVAL; STABILIZATION; MANAGEMENT